"It's Hard Work": A Feminist Political Economy Approach to Reconceptualizing "Work" in the Cancer Context. (April 2019) - Pritlove, Cheryl; Safai, Parissa; Angus, Jan E.; Armstrong, Pat; Jones, Jennifer M.; Parsons, Janet
Within mainstream cancer literature, policy documents, and clinical practice, "work" is typically characterized as being synonymous with paid employment, and the problem of work is situated within the "return to work" discourse. The work that patients perform in managing their health, care, and everyday life at times of illness, however, is largely overlooked and unsupported. Drawing on feminist political economy theory, we report on a qualitative study of 12 women living with cancer. Major findings show that the work of patienthood cut across multiple fields of practice and included both paid and unpaid labor. The most prevalent types of work included illness work, body work, identity work, everyday work, paid employment and/or the work of maintaining income, and coordination work. The findings of this study disrupt popular conceptualizations of work and illuminate the nuanced and often invisible work that cancer patients may encounter, and the health consequences and inequities therein.